Akibat Hukum Penetapan Tanah Musnah: Ganti Rugi atau Dana Kerohiman? - Setiawati, Anda; Probondaru, Ignatius Pradipa; Arsawan, I Gede Yudi; Sihombing, Irene Eka; Nabilah, Hana Jihan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 1 (2025)DO - 10.24843/JMHU.2025.v14.i01.p05, 2025)
The missing of land is one of the causes of the abolition of land rights. With the enactment of Government Regulation Number 18 Year 2021 and Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency of the Republic of Indonesia Number 17 Year 2021, an issue arises where landowners whose land has been missing demand compensation because a national strategic project will be built on the land. The purpose of this study is to explain the legal aspect of land rights over missing land and to provide an overview of the form of compensation given to landowners whose land has been declared missing, whether in the form of compensation or compassion funds. This study employs a normative juridical research method based on secondary data. According to Presidential Regulation Number 52 Year 2022 as amended by Presidential Regulation Number 27 Year 2023, for lands declared missing and intended for construction in the public interest, only compassion funds are provided, as the priority rights of the landowner to reclaim or reconstruct the land are disregarded. Compensation may be provided if the land declared missing is to be used for public interest projects or national strategic projects and has been reclaimed or reconstructed by the landowner. Musnahnya tanah merupakan salah satu penyebab hapusnya hak atas tanah. Dengan diundangkannya Peraturan Pemerintah Nomor 18 Tahun 2021 dan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 17 Tahun 2021 memunculkan persoalan, di mana pemilik tanah yang tanahnya musnah menuntut ganti rugi karena di lokasi tanah akan dibangun proyek strategi nasional. Tujuan dilakukannya kajian ini adalah untuk menjelaskan aspek hukum hak atas tanah dari tanah musnah dan bentuk kompensasi yang diberikan kepada pemilik tanah yang tanahnya terindikasi musnah, apakah dalam bentuk ganti rugi atau berupa dana kerohiman. Dalam kajian ini digunakan metode penelitian yuridis normatif yang berbasis pada data sekunder. Berdasarkan Peraturan Presiden Nomor 52 Tahun 2022 yang sudah diubah dengan Peraturan Presiden Nomor 27 Tahun 2023 untuk tanah-tanah yang terindikasi musnah dan akan digunakan untuk pembangunan demi kepentingan umum, hanya diberikan dana kerohiman karena hak prioritas dari pemilik tanah berupa hak untuk mereklamasi atau merekonstruksi dikesampingkan. Pemberian ganti rugi dapat diberikan dalam kondisi tanah yang terindikasi musnah sudah direkonstruksi atau direklamasi oleh pemilik tanah dan tanah itu akan digunakan untuk pembangunan proyek-proyek demi kepentingan umum atau proyek strategi nasional.